Challenging Role of Women Executives - a Perspective - Sunder, Joyce (Ushus Journal of Business Management, 2002)
In this article the author highlights how women face strong prejudices and discrimination at every stage of their professional career. Thus recommends and calls for major alterations in the deepest and psychological structures instead of the slow subtle changes.